Genetic mapping identifies novel highly protective antigens for an apicomplexan parasite - Blake, D; Billington, K; Copestake, S; Oakes, R; Quail, M; Wan, K; Shirley, M; Smith, A (Public Library of Science, 2011)
Apicomplexan parasites are responsible for a myriad of diseases in humans and livestock; yet despite intensive effort, development of effective sub-unit vaccines remains a long-term goal. Antigenic complexity and our inability to identify protective antigens from the pool that induce response are serious challenges in the development of new vaccines. Using a combination of parasite genetics and selective barriers with population-based genetic fingerprinting, we have identified that immunity against the most important apicomplexan parasite of livestock (Eimeria spp.) was targeted against a few discrete regions of the genome. Herein we report the identification of six genomic regions and, within two of those loci, the identification of true protective antigens that confer immunity as sub-unit vaccines. The first of these is an Eimeria maxima homologue of apical membrane antigen-1 (AMA-1) and the second is a previously uncharacterised gene that we have termed 'immune mapped protein-1' (IMP-1). Significantly, homologues of the AMA-1 antigen are protective with a range of apicomplexan parasites including Plasmodium spp., which suggest that there may be some characteristic(s) of protective antigens shared across this diverse group of parasites. Interestingly, homologues of the IMP-1 antigen, which is protective against E. maxima infection, can be identified in Toxoplasma gondii and Neospora caninum. Overall, this study documents the discovery of novel protective antigens using a population-based genetic mapping approach allied with a protection-based screen of candidate genes. The identification of AMA-1 and IMP-1 represents a substantial step towards development of an effective anti-eimerian sub-unit vaccine and raises the possibility of identification of novel antigens for other apicomplexan parasites. Moreover, validation of the parasite genetics approach to identify effective antigens supports its adoption in other parasite systems where legitimate protective antigen identification is difficult.